The Effects of Auditor Affinity for Client and Perceived Client Pressure on Auditor Proposed Adjustments - Koch, Christopher; Salterio, Steven E. (The Accounting Review, 2017)
ABSTRACT This paper examines how auditors' judgments about accounting policies may differ when experiencing different levels of affinity for client management and facing different levels of pressure from client management. The theory of motivated reasoning is employed to analyze the effects of these two factors that should lead individual auditors to adopt as a directional goal the acceptance of client management's aggressive accounting. Accordingly, we predict and find that auditors experiencing greater client affinity and facing explicit client pressure suggest lower adjustments to clients' aggressive accounting, consistent with motivated reasoning's goal-related predictions. But our study goes further and investigates also how auditors react when motivated reasoning theory's “reasonableness constraint” is potentially violated by auditors who perceive excessive client pressure. We predict and find, consistent with the individual auditor's “reasonable constraint” being triggered in at least some auditors, that perception of client pressure intensity leads those auditors to propose larger adjustments to client accounting. To support our findings, we re-analyze the data from a prior motivated reasoning audit experiment, replicate that study's reported directional goal results employing methods used in this study and, in addition, find similar results to those found in this study for increased client pressure intensity on auditor judgment.